(Re)Presentations of gender and ethnicity in diversity statements on European company websites - Val, Singh; Sébastien, Point (Springer Science Business Media, 2006)
This paper investigates how specific notions of gender and ethnicity are integrated into diversity discourses presented on 241 top European company websites. Large European companies increasingly disclose equality and diversity policies in statements on websites. Such statements may be used to promote an ethical image of the company in terms of how well it manages diversity and guards against discrimination. In this paper, we argue that diversity statement discourses are important as they play a key part in socially constructing how diversity should be regarded in the company by minority and majority groups, as well as indicating corporate values to external stakeholders (investors, government, community, press etc.). Sometimes, the notions of gender or ethnic diversity are positioned as a liability in need of protection, whilst in others, as a source of competitive advantage. We find evidence of use of discursive tools such as problematisation, rationalisation, fixation, reframing and naturalisation of the notions of gender and ethnic diversity, reinforced by use of symbols, such as statistics, photographs, membership badges and awards. Few statements directly associate gender and ethnic diversity with enhanced corporate performance. We found that diversity statements sometimes appear to reinforce existing business stereotypes of women and people from ethnic minorities, and in a few discourses, create new ones, particularly evident in photographs illustrating the diversity web pages.
Keywords: diversity; gender; ethnicity; discourse; corporate websites; Europe